Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Oceanographic features boost latitudinal patterns in copepod body size distribution in the South Atlantic - Érica C. Becker; Luis C. P. Macedo‐Soares; Catarina R. Marcolin; Manoela C. Brandão; Lars Stemmann; Maria G. Mazzocchi; Andrea S. Freire (Limnology and Oceanography, 2024)
The South Atlantic Ocean (SAO) is an under‐sampled ocean where the influence of environmental drivers on copepod body size is poorly understood. This study investigated the body size distribution of copepods from 13°S to 64°S to test Bergmann's rule, which predicts the occurrence of smaller organisms in warmer areas. We hypothesized that additional influence of oceanographic features strengthens this pattern. Zooplankton were sampled during the austral summer from the chlorophyll maximum depth up to the surface, at approximately 100 m depth, using a 200‐ μ m net. The samples were analyzed using the ZooScan imaging system and were classified using the Ecotaxa tool. We estimated copepod family abundance, biomass, and size structure, and their relationships with environmental variables were assessed through generalized linear mixed models (GLMM). Although most copepods increased in size at higher latitudes, not all families followed Bergmann's rule. Small adults of Clausocalanidae, Paracalanidae, Corycaeidae, and Oncaeidae contributed mostly in the Brazil Current (BC), while Calanidae copepodites disproportionately contributed to overall biomass, and Oithonidae adults were the most abundant in high latitudes. Copepod abundance or biomass hotspots were present in the southern limit of the warm BC, at the Subtropical Confluence Zone, and in the subantarctic waters at the Drake passage. Our results suggest that oceanographic features strengthen latitudinal body size relationships due to food availability, and the importance of different life history strategies.

Three major mesoplanktonic communities resolved by in situ imaging in the upper 500 m of the global ocean - Thelma Panaïotis; Marcel Babin; Tristan Biard; François Carlotti; Laurent Coppola; Lionel Guidi; Helena Hauss; Lee Karp‐Boss; Rainer Kiko; Fabien Lombard; Andrew M. P. McDonnell; Marc Picheral; et al. (Global Ecology and Biogeography, 2023)
Aim The distribution of mesoplankton communities has been poorly studied at global scale, especially from in situ instruments. This study aims to (1) describe the global distribution of mesoplankton communities in relation to their environment and (2) assess the ability of various environmental‐based ocean regionalizations to explain the distribution of these communities. Location Global ocean, 0–500 m depth. Time Period 2008–2019. Major Taxa Studied Twenty‐eight groups of large mesoplanktonic and macroplanktonic organisms, covering Metazoa, Rhizaria and Cyanobacteria. Methods From a global data set of 2500 vertical profiles making use of the Underwater Vision Profiler 5 (UVP5), an in situ imaging instrument, we studied the global distribution of large (>600 μm) mesoplanktonic organisms. Among the 6.8 million imaged objects, 330,000 were large zooplanktonic organisms and phytoplankton colonies, the rest consisting of marine snow particles. Multivariate ordination (PCA) and clustering were used to describe patterns in community composition, while comparison with existing regionalizations was performed with regression methods (RDA). Results Within the observed size range, epipelagic plankton communities were Trichodesmium ‐enriched in the intertropical Atlantic, Copepoda‐enriched at high latitudes and in upwelling areas, and Rhizaria‐enriched in oligotrophic areas. In the mesopelagic layer, Copepoda‐enriched communities were also found at high latitudes and in the Atlantic Ocean, while Rhizaria‐enriched communities prevailed in the Peruvian upwelling system and a few mixed communities were found elsewhere. The comparison between the distribution of these communities and a set of existing regionalizations of the ocean suggested that the structure of plankton communities described above is mostly driven by basin‐level environmental conditions. Main Conclusions In both layers, three types of plankton communities emerged and seemed to be mostly driven by regional environmental conditions. This work sheds light on the role not only of metazoans, but also of unexpected large protists and cyanobacteria in structuring large mesoplankton communities.

Global Distribution of Zooplankton Biomass Estimated by In Situ Imaging and Machine Learning - Laetitia Drago; Thelma Panaïotis; Jean-Olivier Irisson; Marcel Babin; Tristan Biard; François Carlotti; Laurent Coppola; Lionel Guidi; Helena Hauss; Lee Karp-Boss; Fabien Lombard; Andrew M. P. McDonnell; et al. (Frontiers in Marine Science, 2022)
Zooplankton plays a major role in ocean food webs and biogeochemical cycles, and provides major ecosystem services as a main driver of the biological carbon pump and in sustaining fish communities. Zooplankton is also sensitive to its environment and reacts to its changes. To better understand the importance of zooplankton, and to inform prognostic models that try to represent them, spatially-resolved biomass estimates of key plankton taxa are desirable. In this study we predict, for the first time, the global biomass distribution of 19 zooplankton taxa (1-50 mm Equivalent Spherical Diameter) using observations with the Underwater Vision Profiler 5, a quantitative in situ imaging instrument. After classification of 466,872 organisms from more than 3,549 profiles (0-500 m) obtained between 2008 and 2019 throughout the globe, we estimated their individual biovolumes and converted them to biomass using taxa-specific conversion factors. We then associated these biomass estimates with climatologies of environmental variables (temperature, salinity, oxygen, etc.), to build habitat models using boosted regression trees. The results reveal maximal zooplankton biomass values around 60°N and 55°S as well as minimal values around the oceanic gyres. An increased zooplankton biomass is also predicted for the equator. Global integrated biomass (0-500 m) was estimated at 0.403 PgC. It was largely dominated by Copepoda (35.7%, mostly in polar regions), followed by Eumalacostraca (26.6%) Rhizaria (16.4%, mostly in the intertropical convergence zone). The machine learning approach used here is sensitive to the size of the training set and generates reliable predictions for abundant groups such as Copepoda (R2 ≈ 20-66%) but not for rare ones (Ctenophora, Cnidaria, R2 < 5%). Still, this study offers a first protocol to estimate global, spatially resolved zooplankton biomass and community composition from in situ imaging observations of individual organisms. The underlying dataset covers a period of 10 years while approaches that rely on net samples utilized datasets gathered since the 1960s. Increased use of digital imaging approaches should enable us to obtain zooplankton biomass distribution estimates at basin to global scales in shorter time frames in the future.

Machine learning techniques to characterize functional traits of plankton from image data - Eric C. Orenstein; Sakina‐Dorothée Ayata; Frédéric Maps; Érica C. Becker; Fabio Benedetti; Tristan Biard; Thibault de Garidel‐Thoron; Jeffrey S. Ellen; Filippo Ferrario; Sarah L. C. Giering; Tamar Guy‐Haim; Laura Hoebeke; et al. (Limnology and Oceanography, 2022)
Plankton imaging systems supported by automated classification and analysis have improved ecologists' ability to observe aquatic ecosystems. Today, we are on the cusp of reliably tracking plankton populations with a suite of lab‐based and in situ tools, collecting imaging data at unprecedentedly fine spatial and temporal scales. But these data have potential well beyond examining the abundances of different taxa; the individual images themselves contain a wealth of information on functional traits. Here, we outline traits that could be measured from image data, suggest machine learning and computer vision approaches to extract functional trait information from the images, and discuss promising avenues for novel studies. The approaches we discuss are data agnostic and are broadly applicable to imagery of other aquatic or terrestrial organisms.

Functional trait‐based approaches as a common framework for aquatic ecologists - Séverine Martini; Floriane Larras; Aurélien Boyé; Emile Faure; Nicole Aberle; Philippe Archambault; Lise Bacouillard; Beatrix E Beisner; Lucie Bittner; Emmanuel Castella; Michael Danger; Olivier Gauthier; et al. (Limnology and Oceanography, 2021)
Aquatic ecologists face challenges in identifying the general rules of the functioning of ecosystems. A common framework, including freshwater, marine, benthic, and pelagic ecologists, is needed to bridge communication gaps and foster knowledge sharing. This framework should transcend local specificities and taxonomy in order to provide a common ground and shareable tools to address common scientific challenges. Here, we advocate the use of functional trait‐based approaches (FTBAs) for aquatic ecologists and propose concrete paths to go forward. Firstly, we propose to unify existing definitions in FTBAs to adopt a common language. Secondly, we list the numerous databases referencing functional traits for aquatic organisms. Thirdly, we present a synthesis on traditional as well as recent promising methods for the study of aquatic functional traits, including imaging and genomics. Finally, we conclude with a highlight on scientific challenges and promising venues for which FTBAs should foster opportunities for future research. By offering practical tools, our framework provides a clear path forward to the adoption of trait‐based approaches in aquatic ecology.

Into the bloom: Molecular response of pelagic tunicates to fluctuating food availability - Paolo Sordino; Salvatore D'Aniello; Eric Pelletier; Patrick Wincker; Valeria Nittoli; Lars Stemmann; Maria Grazia Mazzocchi; Fabien Lombard; Daniele Iudicone; Luigi Caputi (Molecular Ecology, 2020)
The planktonic tunicates appendicularians and thaliaceans are highly efficient filter feeders on a wide range of prey size including bacteria and have shorter generation times than any other marine grazers. These traits allow some tunicate species to reach high population densities and ensure their success in a favourable environment. However, there are still few studies focusing on which genes and gene pathways are associated with responses of pelagic tunicates to environmental variability. Herein, we present the effect of food availability increase on tunicate community and gene expression at the Marquesas Islands (South‐East Pacific Ocean). By using data from the Tara Oceans expedition, we show that changes in phytoplankton density and composition trigger the success of a dominant larvacean species (an undescribed appendicularian). Transcriptional signature to the autotroph bloom suggests key functions in specific physiological processes, i.e., energy metabolism, muscle contraction, membrane trafficking, and proteostasis. The relative abundance of reverse transcription‐related Pfams was lower at bloom conditions, suggesting a link with adaptive genetic diversity in tunicates in natural ecosystems. Downstream of the bloom, pelagic tunicates were outcompeted by copepods. Our work represents the first metaomics study of the biological effects of phytoplankton bloom on a key zooplankton taxon.

Are tropical coastal reefs sinks or sources of mesozooplankton? A case study in a Brazilian marine protected area - Gleice S. Santos; Lars Stemmann; Fabien Lombard; Ralf Schwamborn (Coral Reefs, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

The Seasonal and Inter-Annual Fluctuations of Plankton Abundance and Community Structure in a North Atlantic Marine Protected Area - Fabio Benedetti; Laëtitia Jalabert; Marc Sourisseau; Beatriz Becker; Caroline Cailliau; Corinne Desnos; Amanda Elineau; Jean-Olivier Irisson; Fabien Lombard; Marc Picheral; Lars Stemmann; Patrick Pouline (Frontiers in Marine Science, 2019)

Particulate matter flux interception in oceanic mesoscale eddies by the polychaete Poeobius sp. - Svenja Christiansen; Henk‐Jan Hoving; Florian Schütte; Helena Hauss; Johannes Karstensen; Arne Körtzinger; Simon‐Martin Schröder; Lars Stemmann; Bernd Christiansen; Marc Picheral; Peter Brandt; Bruce Robison; et al. (Limnology and Oceanography, 2018)
Gelatinous zooplankton hold key functions in the ocean and have been shown to significantly influence the transport of organic carbon to the deep sea. We discovered a gelatinous, flux‐feeding polychaete of the genus Poeobius in very high abundances in a mesoscale eddy in the tropical Atlantic Ocean, where it co‐occurred with extremely low particle concentrations. Subsequent analysis of an extensive in situ imaging dataset revealed that Poeobius sp. occurred sporadically between 5°S–20°N and 16°W–46°W in the upper 1000 m. Abundances were significantly elevated and the depth distribution compressed in anticyclonic modewater eddies (ACMEs). In two ACMEs, high Poeobius sp. abundances were associated with strongly reduced particle concentrations and fluxes in the layers directly below the polychaete. We discuss possible reasons for the elevated abundances of Poeobius sp. in ACMEs and provide estimations showing that a single zooplankton species can completely intercept the downward particle flux by feeding with their mucous nets, thereby substantially altering the biogeochemical setting within the eddy.

New insights into global biogeography, population structure and natural selection from the genome of the epipelagic copepod Oithona - Mohammed‐Amin Madoui; Julie Poulain; Kevin Sugier; Marc Wessner; Benjamin Noel; Leo Berline; Karine Labadie; Astrid Cornils; Leocadio Blanco‐Bercial; Lars Stemmann; Jean‐Louis Jamet; Patrick Wincker (Molecular Ecology, 2017)
In the epipelagic ocean, the genus Oithona is considered as one of the most abundant and widespread copepods and plays an important role in the trophic food web. Despite its ecological importance, little is known about Oithona and cyclopoid copepods genomics. Therefore, we sequenced, assembled and annotated the genome of Oithona nana . The comparative genomic analysis integrating available copepod genomes highlighted the expansions of genes related to stress response, cell differentiation and development, including genes coding Lin12‐Notch‐repeat ( LNR ) domain proteins. The Oithona biogeography based on 28S sequences and metagenomic reads from the Tara Oceans expedition showed the presence of O. nana mostly in the Mediterranean Sea ( MS ) and confirmed the amphitropical distribution of Oithona similis . The population genomics analyses of O. nana in the Northern MS , integrating the Tara Oceans metagenomic data and the O. nana genome, led to the identification of genetic structure between populations from the MS basins. Furthermore, 20 loci were found to be under positive selection including four missense and eight synonymous variants, harbouring soft or hard selective sweep patterns. One of the missense variants was localized in the LNR domain of the coding region of a male‐specific gene. The variation in the B‐allele frequency with respect to the MS circulation pattern showed the presence of genomic clines between O. nana and another undefined Oithona species possibly imported through Atlantic waters. This study provides new approaches and results in zooplankton population genomics through the integration of metagenomic and oceanographic data.

Optical imaging of mesopelagic particles indicates deep carbon flux beneath a natural iron‐fertilized bloom in the Southern Ocean - Marie-Paule Jouandet; Thomas W. Trull; Lionel Guidi; Marc Picheral; Friederike Ebersbach; Lars Stemmann; Stéphane Blain (Limnology and Oceanography, 2011)
We recorded vertical profiles of size distributions of particles (ranging from 0.052 to several mm in equivalent spherical diameter) in the natural iron‐fertilized bloom southeast of Kerguelen Island (Southern Ocean) and in surrounding high‐nutrient, low‐chlorophyll (HNLC) waters with an Under Water Video Profiler during the Kerguelen Ocean and Plateau Compared Study cruise (Jan–Feb 2005). Total particle numerical abundance and total particle volume (TPV) in the 0–200‐m layer were respectively 3‐fold and 20‐fold higher in the bloom, and integrated TPV was correlated to integrated chlorophyll concentration. The difference persisted well into the ocean interior with a 10‐fold higher TPV at 400‐m depth beneath the natural iron‐fertilized bloom. Below 400 m, increases in TPV values at the bloom stations reflect the suspension of bottom sediments. Bloom waters had a greater proportion of large particles from the surface to 400 m and also exhibited an increase of this proportion with depth compared to HNLC waters. Multiple visits to the bloom reference Sta. A3, suggest preferential removal of large particles as the bloom declined. Comparing our particle abundance size spectra with those observed previously in polyacrylamide gel‐filled sediment traps allows us to estimate mesopelagic particle sinking rates. These results suggest that particles sink faster in the HNLC waters than beneath the bloom. The fact that sinking speeds were not a simple monotonic function of particle size and varied spatially highlights the need to go beyond parameterizations of sinking rate as a function of size alone.

Experimental and modeling evidence of appendicularian‐ciliate interactions - Fabien Lombard; Damien Eloire; Angelique Gobet; Lars Stemmann; John R. Dolan; Antoine Sciandra; Gabriel Gorsky (Limnology and Oceanography, 2010)
Interactions between appendicularians and ciliates were observed over the life span of Oikopleura dioica in laboratory cultures and clarified with the use of mathematical modeling and microscopic observations. Complex interactions including competition, parasitism, predation, and histophagy occurred simultaneously, resulting in apparent mutualism. The large ciliate Strombidium sp. entered the inlet filters of appendicularian houses (larger than 500 µm body size) by distorting the mesh. Once inside, Strombidium fed on particles concentrated on the filters. When appendicularians were larger than 900 µm, both the high flow rate in the buccal tube and their esophagus width allowed the "host" appendicularian to capture and ingest ciliates. Thus, ciliates seem to be sequentially competitors, then parasites or commensal in appendicularian houses, and finally prey for appendicularians. Appendicularian rates of somatic growth and reproduction were enhanced when ciliates were ingested. This additional food supply could be essential in oligotrophic environments. Reciprocally, appendicularians support higher ciliate growth rates, allowing ciliates to survive and grow in food‐limited environments. Appendicularians thus modify the size spectrum of the microbial food web both by removing small organisms (0.2‐30 µm) and enhancing the growth of mid‐sized and large ciliates.

Effects of phytoplankton community on production, size, and export of large aggregates: A world‐ocean analysis - Lionel Guidi; Lars Stemmann; George A. Jackson; Frédéric Ibanez; Hervé Claustre; Louis Legendre; Marc Picheral; Gabriel Gorskya (Limnology and Oceanography, 2009)
We recorded vertical profiles of size distributions of large particles ( a in the euphotic zone. We found that coefficient k in the Martin power relationship, which describes the decrease in the vertical mass flux with depth, varies between 0.2 and 1.0 in the world ocean, and we provided an empirical relationship to derive k from the size structure of phytoplankton biomass in the euphotic zone. Biogeochemists and modelers could use that relationship to obtain a realistic description of the downward particle flux instead of using a constant k value as often done.

Vertical distribution of aggregates (>110 µm) and mesoscale activity in the northeastern Atlantic: Effects on the deep vertical export of surface carbon - Lionel Guidi; Lars Stemmann; Louis Legendre; Marc Picheral; Louis Prieur; Gabriel Gorsky (Limnology and Oceanography, 2007)
Spatial and temporal variability in the distribution of marine aggregates (>110 mm) was studied using underwater video profilers in an area off the Iberian Peninsula and Azores Islands dominated by mesoscale and submesocale hydrodynamics in winter, spring, and summer 2001. In the 0‐200‐m layer, aggregates were most abundant in spring (100‐120 mg dry weight [dry wt] m ‐3 ) and lowest during summer and winter (1‐10 mg dry wt mm ‐3 ). In the deeper layers (down to 1,000 m), the seasonal pattern was different, with concentrations highest in spring and summer, and lowest in winter (e.g., at 800 m, 5‐10 mg dry wt mm ‐3 in spring and summer; 1‐5 mg dry wt mm ‐3 in winter). The seasonal change in the abundance of aggregates in the upper 1,000 m was consistent with changes in the composition and intensity of the particulate flux recorded in sediment traps and with seasonal changes in the surface phytoplankton community. In an area dominated by eddies, surface accumulation of aggregates and export down to 1,000 m occur at mesoscale distances (